ثورة القَاضي جَعفَر بن عبد الله بن جَحاف المَعَافْرِي في بَلَنْسِيَة ( 485 - 487 ه / 1092 - 1094 م) - شهبي, عبد العزيز; كربوعة, سالم (Sciences de l'Homme et de la Société, 2017)
يتناول هذا البحث ثورة القاضي أبو جعفر ابن جحاف في مدينة فالنسيا، وذلك بعد نهاية عصر ملوك الطوائف في الأندلس، وفترة سيطرة المرابطين عليها. وقد طمح هذا الفقيه إلى تأسيس مملكة والاستقلال بمدينة فالنسيا، لكنه لم ينجح لأنه لم يكن رجل سياسة ولا رجل حرب، فاستمرت دولته سنتان فقط، إلى أن جاء السيد القمبيطور، حيث تمكن من انتزاع المدينة منه وقتله حرقا سنة 487 هـ / 1094 م .   Abstract :   This research deals with the jurist Abu Jaafar Ibn Djahaaf revolution in the city of Valencia, after the end of the era of kings of Denominations in Andalusia, and Marabouts’ control on it. This jurist has aspired to the founding of a Kingdom independently in Valencia, but it did not work because he was neither a politician nor a man of war,  so, his state brought into being only for two years, till the coming of Mr. El Cid Campeador, when he managed to wrest the city and kill him burned to death in 1094.